2017
DOI: 10.1103/physrevb.96.045440
|View full text |Cite
|
Sign up to set email alerts
|

Spin-dependent coupling between quantum dots and topological quantum wires

Abstract: Considering Rashba quantum wires with a proximity-induced superconducting gap as physical realizations of Majorana bound states and quantum dots, we calculate the overlap of the Majorana wave functions with the local wave functions on the dot. We determine the spin-dependent tunneling amplitudes between these two localized states and show that we can tune into a fully spin polarized tunneling regime by changing the distance between dot and Majorana bound state. Upon directly applying this to the tunneling mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 59 publications
2
66
0
Order By: Relevance
“…Weakness of each of the transport channels of QD will depend on the asymmetry in spin tunneling between the QD and MBS. As Klinovaja and co‐authors shown, the spin up and down tunneling amplitudes between MBS and quantum dot depend on the spin–orbit interaction length. The change of distance between the dot and topological section hosting MBS causes the oscillations of tunneling amplitudes and especially it can lead to the full‐polarization of tunneling amplitudes.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Weakness of each of the transport channels of QD will depend on the asymmetry in spin tunneling between the QD and MBS. As Klinovaja and co‐authors shown, the spin up and down tunneling amplitudes between MBS and quantum dot depend on the spin–orbit interaction length. The change of distance between the dot and topological section hosting MBS causes the oscillations of tunneling amplitudes and especially it can lead to the full‐polarization of tunneling amplitudes.…”
Section: Introductionmentioning
confidence: 92%
“…The dot electron hybridizes also with Majorana wire giving the coupling parameter tmσ=πρdσ|VσM|2 where ρ dσ is the density of states of the quantum dot. In our considerations we assume that the Majorana coupling parameter is dependent on the spin direction of dot electron centertnormalm=tnormalm0(1p)centertnormalm=tnormalm0p where t m0 is phenomenological constant describing the maximum tunneling between the quantum dot and Majorana wire.…”
Section: Theoretical Descriptionmentioning
confidence: 99%
See 3 more Smart Citations